2011
DOI: 10.1159/000331724
|View full text |Cite
|
Sign up to set email alerts
|

DHA Protects Against Zinc Mediated Alterations in Neuronal Cellular Bioenergetics

Abstract: Zinc accumulation may impair cellular bioenergetics, which is associated with neuronal apoptosis. We simultaneously assessed anaerobic and aerobic metabolism in live cells to characterise this effect and hypothesised that the omega 3 fatty acid docosahexaenoic acid (DHA) would protect against any zinc mediated alterations in bioenergetics. In this study we observed a decrease in cellular oxygen consumption, but not glycolytic rate, following chronic zinc exposure, which was specific for neuronal cells. This wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 21 publications
(25 reference statements)
0
23
0
Order By: Relevance
“…Recently, we have reported that DHA could protect against zinc-altered mitochondrial dysfunction in M17 cells [10]. Part of this effect could be due to the neuroprotective function of DHA in limiting cellular zinc uptake through decreasing ZnT-3 zinc transporter expression levels [6,20], which in turn inhibits zinc toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have reported that DHA could protect against zinc-altered mitochondrial dysfunction in M17 cells [10]. Part of this effect could be due to the neuroprotective function of DHA in limiting cellular zinc uptake through decreasing ZnT-3 zinc transporter expression levels [6,20], which in turn inhibits zinc toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of zinc toxicity is unknown, but evidence suggests that zinc induces cellular apoptosis through inhibition of adenosine triphosphate (ATP) synthesis [8,9], increase in the production of reactive oxygen species (ROS) and eventual loss of mitochondrial membrane potential ∆Ψ m [9]. Recently, we reported that DHA protects against zinc-mediated alterations in human neuronal cell bioenergetics and mitochondrial function [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Following standardization using an established protocol, the basal oxygen consumption (‘respiratory’) rate in xL3s was measured using the Seahorse XF24 flux analyser (Seahorse Biosciences, USA) (McGee et al., 2011). In brief, 450 μl of LB* + 1% DMSO containing 100 μM of tolfenpyrad (‘hit’ compound) or 100 μM of moxidectin (control; not known to inhibit respiration), or LB* + 1% DMSO alone (untreated control) were transferred in quadruplicate to the wells of a 24-well plate (Seahorse XF24).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were washed and incubated at 37°C in DMEM containing either 5 mmol/L glucose, 1 mmol/L pyruvate, and 1 mmol/L glutamate or 25 mmol/L glucose, 1 mmol/L pyruvate, and 1 mmol/L glutamate, pH 7.4, for 2 h. Three basal OCR measurements were performed, and these were then repeated following sequential exposure to the ATP synthase inhibitor oligomycin (1 mmol/L), the proton ionophore FCCP (1 mmol/L), and the complex III inhibitor antimycin A (1 mmol/L). Calculations of the respiratory parameters of mitochondrial function were then completed (27). At the end of the assay, the number of cells was determined in each well using the CyQuant Cell Proliferation Assay kit (Molecular Probes) according to the instructions of the manufacturer.…”
Section: Lentiviral Infection Of Ptecs and Cellular Oxygen Consumptionmentioning
confidence: 99%